Some Comments on Saaty's AHP - Pérez, Joaquin (Management Science, 1995)
The purpose of this short paper is to help clarify some questions which have arisen with respect to the suitability, or even the correctness, of the way Saaty's AHP method handles criteria weights, sometimes causing the rank reversal phenomenon. The position set forth in this paper is that this undesirable effect does not, per se, invalidate that method, but it does make it necessary to identify the kind of situations in which the method is suitable.